2023
DOI: 10.1080/21645515.2023.2232247
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 producing immunotherapy improves ex vivo T cell functions of immunosenescent patients, especially post hip fracture

Chrystel Marton,
Alix Minaud,
Charles-Antoine Coupet
et al.

Abstract: Following acute stress such as trauma or sepsis, most of critically ill elderly patients become immunosuppressed and susceptible to secondary infections and enhanced mortality. We have developed a virus-based immunotherapy encoding human interleukin-7 (hIL-7) aiming at restoring both innate an adaptative immune homeostasis in these patients. We assessed the impact of this encoded hIL-7 on the ex vivo immune functions of T cells from PBMC of immunosenescent patients with or without hip fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
0
0
Order By: Relevance
“…Remarkably, previous studies have shown that IL-7 administration can reverse sepsis-induced lymphopenia by inhibiting apoptosis and improving the proliferation of T lymphocytes, which was recently demonstrated in a clinical trial [ 29 , 30 ]. In addition, IL-7 increases the activation and promotes the rejuvenation of T cells in patients with immunosenescence, as reported by Marton et al [ 31 ]. Considering both aggravated immune cell apoptosis and profound immune exhaustion in elderly patients, with sepsis, IL-7 may be an underlying immunotherapeutic strategy, and its efficacy is highly anticipated.…”
Section: Discussionmentioning
confidence: 55%
“…Remarkably, previous studies have shown that IL-7 administration can reverse sepsis-induced lymphopenia by inhibiting apoptosis and improving the proliferation of T lymphocytes, which was recently demonstrated in a clinical trial [ 29 , 30 ]. In addition, IL-7 increases the activation and promotes the rejuvenation of T cells in patients with immunosenescence, as reported by Marton et al [ 31 ]. Considering both aggravated immune cell apoptosis and profound immune exhaustion in elderly patients, with sepsis, IL-7 may be an underlying immunotherapeutic strategy, and its efficacy is highly anticipated.…”
Section: Discussionmentioning
confidence: 55%